Incidence, clinical profile and short term outcome of cerebral abscess in cyanotic congenital heart diseases - Rumana Sangi; Aliya Kemal Ahsan; Abdul Sattar Shaikh; Ali Raza; Hussain Bux Korejo; Veena Kumari; Musarat Nazir Sandano; Ume Rubab Sandano (Heliyon, 2023)
Background: Brain abscess is a serious infection of brain parenchyma in patients with cyanotic congenital heart disease (CCHD) and around 25–46 % of unrepaired CCHD patients develop brain abscess. Aim of this study was to determine the incidence, clinical features, microbiology and factors associated with early and short term outcome of cerebral abscess in CCHD. Method: ology: This is a retrospective study, conducted at Pediatric cardiology department, National Institute of Cardiovascular Diseases (NICVD) Karachi. The data was collected from January 2019 to December 2021. All CCHD patients between 1 and 25 years of age were included. Data of patients with cerebral abscess was reviewed. Results: Among the 544 pediatric patients hospitalized in the last two years, brain abscesses were identified in 51 (9.3 %). Polycythemia (31.4 %) was the most significant contributing factor, especially in patients aged above 10 years. The most frequently seen CCHD was tetralogy of fallot (TOF) 60.8 %. Majority of the patients (84.3 %) had a single abscess while 15.7 % had multiple abscesses. E coli (9.7 %) was the most common isolated pathogen. Immediate complication identified was cerebral edema in 22 (43.1 %). Four patients (7.8 %) died, 47 (92.2 %) patients completed treatment course. 45.1 % had complete recovery however, 17 (33.3 %) had neurological deficits, 8 (15.7 %) had seizures and 2 (3.9 %) patients had residual abscess. Prolonged hospitalization was observed in patients of age group <10 years. Conclusion: In patients with underlying CCHD,early referrals and intervention are key to mitigating the severe consequences of cerebral abscesses and can drastically improve patient outcomes.